Aiming factor to flatten the flux distribution on cylindrical receivers. (15th June 2018) - Sánchez-González, Alberto; Rodríguez-Sánchez, María Reyes; Santana, Domingo
Abstract: High incident flux gradients and hot spots lead to extreme thermal stresses that may damage and reduce the lifetime of central receivers. An aiming strategy based on a single parameter, k, named aiming factor, is developed to generate symmetric flux maps about the receiver equator. By means of this k factor, ranging between 3 (generally equivalent to equatorial aiming) and 0 (alternatively aiming to top and bottom borders), the solar flux incident on the receiver and the spillage losses can be controlled. For each sector in a heliostat field, the aiming factor values causing the flattest symmetric flux maps, k f l a t, are deterministically found with a sweep and mesh shifting procedure. Results for Dunhuang solar power tower plant show that k f l a t is fairly constant throughout the year, except near sunrise and sunset in east and west sectors, respectively./ Graphical abstract: Image 1 Highlights: Single parameter to aim all the heliostats in a field with uniform spillage. Flat flux distribution on central receivers. Mesh shifting procedure to save computation time. Implemented in FluxSPT freeware tool.